Digital Fluency in Open, Flexible and Distance Learning - Alison J Fields; Maggie Hartnett (Flexible Learning Association of New Zealand, 2018)
Digital fluency affects us all - as our world becomes more online, our skills to be able to navigate in this world may determine how well we participate, contribute and succeed. In this Editorial we look at the Digital Technologies Hangarau Matihiko Curriculum being introduced to primary and secondary schools in New Zealand and ask what this means for the open, flexible and distance learning sectors. We also celebrate the JOFDL Best Paper Awards for 2018 which were presented at the biennial FLANZ Conference in Palmerston North earlier this year. The Editorial is rounded off with an overview of the articles in this issue.